(untitled) (FAVE Sección Ciencias Agrarias, 2024)
Given the growth in the size of the dairy farms, the increase in hired labor, and considering its importance in the results of the activity, from the Agency Theory, the hypothesis was postulated that the increase in the size of the establishments favors the separation between ownership and control, causing agency problems and in the internal organization of dairy establishments. The objective was to describe and relate the organizational architecture of the dairy establishments in the Argentine Pampas region with their size and to identify agency problems. A descriptive and cross-sectional study was carried out from the Dairy Sector Survey 2016-2017 of INTA on a total of 163 personal interviews with dairy managers in the Pampas region. The hypothesis was partially confirmed, since the increase in the size of the dairy company favors the separation of ownership and administration of milking and feeding tasks, but not economic management. As the number of total cows increased, costs and agency problems increased, although there was decision-making that accompanied specific knowledge in milking and feeding. The greater the size, was the better the task assignment mechanisms, the economic and non-economic incentives, as well as the control over the productive process, although not over the performance of the personnel. It is essential to adjust the organizational architecture with the increase in scale and more hired labor, and not maintain it over time.